Redo surgery after low anterior resection for chronic pelvic sinus and anastomotic disruption. Could pull-through procedure with delayed anastomosis be a feasible alternative? Case reports and narrative review. (April 2022) - Banchini, Filippo; Luzietti, Enrico; Conti, Luigi; Palmieri, Gerardo; Capelli, Patrizio
Abstract: Introduction: A considerable step forward in low rectal cancer resection has been done in the last decades. Maintaining total mesorectal excision as the gold standard treatment, new techniques such as Trans-Anal Mini-Invasive Surgery (TAMIS) and Trans-Anal Total Mesorectal Excision (TATME), which have been added to improve skills in laparoscopic and robotic surgery, currently represent the advancement of this procedure. Despite improvements in surgical techniques, complications after low anterior resection for rectal cancer still remain a challenge. Drainage and colostomy are the main treatments used to overcome the problem caused by anastomosis failure, and most patients will never been restored. Different techniques of redo surgery could be proposed to deal complex cases, although remaining high risk procedures. Case presentation: We present two clinical cases with a late complication of the colorectal anastomosis: one with a late leakage of low colorectal anastomoses, treated with Hartman procedure, that developed a pelvic chronic sinus; the another one with complete anastomotic disruption after massive suture bleeding; both treated with delayed pull-through anastomosis, according to Turnbull-Cutait technique. We also made a review of relative literature, in order to back our therapeutic iters. Discussion: Both the procedures were carried out satisfactorily, with restoration of intestinal continuity and good anastomotic result. It allows the resolutions of the chronic sepsis caused by the pelvic sinus and maintenance of intestinal continuity with a good Wexner incontinence score. Literary review demonstrated that this procedure still remains undervalued and not widely exploited. Conclusion: Delayed pull-through coloanal anastomosis could be considered as a valid option, in order to preserve intestinal continuity in septic or complicated low colorectal anastomosis. Highlights: Complications after colorectal anastomosis, such as septic leakage or anastomotic disruption, remain a problem to deal with for colorectal surgeons. Conversion to terminal colostomy is the most frequent option chosen, but the most of time restoration of bowel continuity is not performed. Delayed coloanal anastomosis with pull-through procedure described by Turnbull-Cutait might be an option to consider in difficult situations, to maintain or to restore intestinal continuity and could be also chosen as a first option for coloanal anastomosis.